Ureido group-specific antibodies are induced in rabbits immunized with citrulline- or homocitrulline-containing antigens. (2nd October 2016) - Turunen, Sanna; Koivula, Marja-Kaisa; Risteli, Leila; Risteli, Juha
Abstract: The specificities and cross-reactions of antibodies induced by citrulline- and homocitrulline-containing proteins may give implications on the role of citrulline- and homocitrulline-binding antibodies in the pathogenesis and progression of rheumatoid arthritis (RA). Here we use rabbits as an experimental model of antibody development in RA. Thirty-two animals were immunized with peptide antigens containing either homocitrulline or citrulline. The sera were tested for binding to CCP and MCV antigens and to peptide sequences related to carboxyterminal telopeptides of type I and II collagens and containing arginine, citrulline, or homocitrulline. The binding of CCP and MCV antigens to antisera against homocitrulline-containing immunogens could be inhibited by human serum albumin containing homocitrulline, whereas similar binding to sera against citrulline-containing immunogens was not inhibited. The antisera induced with citrulline-containing collagen telopeptides recognized type I collagen-related antigens in a sequence-specific manner, as antibody binding to both citrulline- and homocitrulline-containing peptides was inhibited by corresponding citrullinated and native peptides. In contrast, type II collagen-related peptides were recognized by the antisera in a ureido group-specific manner, as their binding to homocitrulline-containing peptide was inhibited by both citrulline- and homocitrulline-containing, but not native peptide. Binding of the citrullinated type II collagen peptide could only be inhibited by the similarly citrullinated peptide. In conclusion, antibodies induced with citrulline or homocitrulline-containing antigens bound antigens in a ureido group-specific manner, recognizing citrulline and homocitrulline also in other sequences than those used in the original immunization. In competitive situations the amino acid present in the immunization antigen was favored.